English Language Needs of Information Systems Students for Future Careers in the AI Era - Ditta Mustika Rakhmawati; Murtini Murtini; Ihsan Rolis; Erma Damayanti; Artipah Artipah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The rapid integration of artificial intelligence (AI) into higher education and professional environments has transformed the role of English from a traditional academic subject into a critical competency for technology-driven careers. This study aimed to identify the English language needs of Information Systems students for future careers in the AI era. Employing a quantitative descriptive survey design, data were collected from 80 undergraduate Information Systems students at a private higher education institution in South Jakarta, Indonesia. A structured questionnaire was used to examine students’ perceived needs in four areas: speaking skills, writing skills, reading skills, and AI-related English skills. The data were analyzed using descriptive statistics, including frequencies, percentages, means, and standard deviations. The findings revealed that all four competencies were perceived as important for future professional development. However, AI-related English skills emerged as the highest-ranked competency (M = 4.56), followed by speaking skills (M = 4.45), writing skills (M = 4.28), and reading skills (M = 4.10). The results suggest that students increasingly view English as an essential tool for interacting with AI technologies, accessing global knowledge, and participating in digital workplaces. The study highlights the need for English language curricula in Information Systems programs to incorporate AI-assisted communication and technology-oriented professional language skills to better prepare graduates for the evolving demands of the AI era.